2020
DOI: 10.1148/radiol.2020200287
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences and Tumor Blood Flow from Dynamic Susceptibility Contrast MRI Are Associated with Treatment Response after Chemoradiation and Long-term Survival in Rectal Cancer

Abstract: I n 2018, rectal cancer was the eighth most common cancer in the world (1). Survival rates have increased in the past decade mainly because of total mesorectal excision surgery and neoadjuvant treatment, when indicated. However, patients with metastatic disease remain a challenge. Norwegian patients with metastatic rectal cancer have a 5-year survival rate of 18.3% for men and 20.6% for women (2). To enable a more adapted treatment, there is a need to assess individual tumor characteristics that can be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
2
15
0
Order By: Relevance
“…(18-20) Tumors with poor blood perfusion has less oxygen and nutrients, and the tumor has more severe hypoxia, thus mobilizing the tumor cells to leave the primary site to nd a more suitable survival site. (15) Tumors with poor prognosis have less blood ow, causing less blood re ux. Hence, there was no signi cant change in the drainage vein, and the diameter of the re ux vein was small.…”
Section: Discussionmentioning
confidence: 99%
“…(18-20) Tumors with poor blood perfusion has less oxygen and nutrients, and the tumor has more severe hypoxia, thus mobilizing the tumor cells to leave the primary site to nd a more suitable survival site. (15) Tumors with poor prognosis have less blood ow, causing less blood re ux. Hence, there was no signi cant change in the drainage vein, and the diameter of the re ux vein was small.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CXCL7 has been proposed as a circulating biomarker for CRC detection [46]. With regard to vascular processes, we recently showed that hemodynamic factors of the rectal cancer differ and result in distinctive outcomes in men and women [47,48]. In our previous vitamin D study, a weak inverse correlation between circulating 25(OH) D and SIR markers appeared in all patients analyzed together [13]-it might be that stronger and more distinct modes of systemic inflammation with respect to the vitamin D status had been revealed if male and female patients had been analyzed separately.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the ROC value in pre-treatment kurtosis was significantly higher than all other parameters (0.907, p < 0.001) [147]. Another prospective observational cohort study found that a lower baseline tumour blood flow from dynamic susceptibility contrast MRI was associated with better response to nCRT (p = 0.01) [148].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 94%